Dynamics of microbial populations and metabolites of fermenting saps throughout tapping process of ron and oil palm trees in Côte d’Ivoire - Djeni, Theodore N.; Keisam, Santosh; Kouame, Karen H.; Assohoun-Djeni, Christelle Nanouman; Ake, Francine D. M.; Amoikon, Laurent S. T.; Tuikhar, Ngangyola; Labala, Rajendra K.; Dje, Marcellin K.; Jeyaram, Kumaraswamy (Frontiers in Microbiology, 2022)
Palm wine fermentation is a complex microbial process that evolves with tapping times. The dynamics in microbiota and metabolites throughout palm wine tapping days is still not established, which are critical for the distinctive characteristics of palm wine taste and quality, and thus the mastery of the daily quality fluctuation during tapping. We analysed the changes in microbial community structure by amplicon sequencing of bacterial 16S rRNA gene and fungal internal transcribed spacer (ITS) region, and metabolite profile changes using mass spectrometry in palm wine collected over 25-30 days tapping of ron (Borassus aethiopum) and oil palms (Elaeis guineensis) from Côte d’Ivoire. The stage-wise collected palm wine samples showed distinct changes in microbial diversity and pH, supporting microbial community dynamics during palm wine tapping. Results highlighted the dominance of Saccharomyces cerevisiae in early stages and the emergence of non-Saccharomyces yeasts, particularly Hanseniaspora spp. in the later stages of oil palm wine tapping, vice versa in the case of ron palm wine tapping, with a unique presence of Saccharomycodes in the later stages (15-30 days). Fructophilic lactic acid bacteria (FLAB), mainly Fructobaillus and Leuconostoc, encountered in both types of palm wine tapping showed a decline at later stages of oil palm wine tapping. In this type of palm wine, acetic acid bacteria with genera Acetobacter and Glucanoacetobacter, by surpassing Lactobacillus in the last stage become dominant, whereas Lactobacillus remained dominant in ron palm wine throughout tapping days. The decline in the relative abundance of gevotroline and essential amino acids during the later stages of palm wine tapping (15-25 days) supports the difference in the health benefits of the palm wine obtained from different days of tapping, indicating that early stages of tapping is more nutritional and healthy than the later stages. The microbial dynamics may be a potential indicator of metabolite changes during palm sap fermentation, thus contributing to establish particular features of palm wines in different stages of tapping. This understanding of microbial ecology and chemical composition changes during palm wine tapping can be used as biomarkers to assess palm wine's quality and help to design an optimum starter culture.